PELAKSANAAN MOTIVASI OLEH CAMAT PADA KANTOR CAMAT MAJA KABUPATEN MAJALENGKA - Firman Yudhanegara (Jurnal Ilmu Administrasi CENDEKIA, 2017)
AbstractBased on regulation n. 10/2009 of the Majalengka Regency related to the organization of the Majalengka regency, the sub-district is a Regional Regency apparatus as a regional technical implementer that has a specific work area run by a Camat that is domiciled below and is responsible before the regent through the regional secretary.The purpose of this study was to determine the implementation of Camat's motivation with the performance of employees in the office of Maja Camat in the Majalengka Regency. The results were obtained 1) the implementation of the motivation of Camat was not carried out optimally and when applying the principles of motivation there were still gaps between the principles of motivation, which include: a) the principle of inclusion in the process of decision making; b) the principle of communication in support of the circulation of information about work; c) principle of recognition and appreciation of work; d) the principle of authority has delegated the task of fostering a sense of trust; e) the principle of mutual attention as a form of respect and mutual respect; 2) the principles of motivation are not yet fully implemented because Camat has to face several obstacles; And 3) there are obstacles, so Camat strives to improve the performance of the employees of the office of Maja Camat in the Majalengka Regency. Keywords: implementation, motivation, employee performance. AbstrakBerdasarkan Peraturan Daerah Kabupaten Majalengka Nomor 10 Tahun 2009 tentang Organisasi Perangkat Daerah Kabupaten Majalengka, Kecamatan adalah merupakan perangkat Daerah Kabupaten sebagai pelaksana teknis kewilayahan yang mempunyai wilayah kerja tertentu dipimpin oleh seorang Camat yang berkedudukan di bawah dan bertanggungjawab kepada Bupati melalui Sekretaris Daerah.Tujuan dari penelitian ini adalah untuk mengetahui pelaksanaan motivasi Camat dengan kinerja pegawai pada kantor Camat Maja Kabupaten Majalengka. Hasil penelitian diperoleh 1) pelaksanaan motivasi Camat belum optimal dilakukan dan dalam penerapan asas - asas motivasi masih adanya kesenjangan diantara asas-asas motivasi diantaranya: a) asas mengikutsertakan dalam pengambilan keputusan; b) asas komunikasi dalam menunjang sirkulasi informasi pekerjaan; c) asas pengakuan dan apresiasi pekerjaan; d) asas wewenang yang didelegasikan tugas untuk menumbuhkan rasa kepercayaan diri; e) asas perhatian timbal balik sebagai bentuk saling menghormati dan menghargai; 2) belum diterapkannya asas – asas motivasi secara penuh dikarenakan Camat mengadapi beberapa hambatan; Dan 3) terdapatnya hambatan maka terdapat upaya Camat dalam meningkatkan kinerja pegawai pada Kantor Camat Maja Kabupaten Majalengka. Kata Kunci: Pelaksanaan, Motivasi, Kinerja Pegawai